INFORMATION ON GOODS DELIVERY SYSTEM PT.GARMEN - Suyanto Suyanto; Ir. Don Elsyafitri (Jurnal Sistem Informasi, 2002)
Search duration data delivery warehouse staff needed to provide information to the staff of the seller if needed because the amount of work done so far with the manual method by warehouse staff, are obstacles that were found in a running system. other than that with this new system, the warehouse staff is no longer expected difficulties to obtain the required information, including the minimum inventory.